2009
DOI: 10.4103/0253-7184.62764
|View full text |Cite
|
Sign up to set email alerts
|

RTI/STI prevalence among urban and rural women of Surat: A community-based study

Abstract: Objectives:To estimate the prevalence of RTI/STI among women in urban and rural areas of Surat and analyze the influence of socioeconomic, socio-demographic and other determinants possibly related to RTI/STI.Method:A community-based cross-sectional study. Women aged 15-49 years (n = 102) were interviewed and underwent a gynecological examination. Specimens were collected for laboratory diagnosis of chlamydia, gonorrhea, trichomonas, bacterial vaginosis (BV), candidiasis, hepatitis B, HIV, and syphilis.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 2 publications
6
31
2
Order By: Relevance
“…In our study, multiple sexual partner as a risk factor was found in 15% of the study population, while according to the study in urban Rwanda, it is found to be as high as 33% 4 In our study, STI prevalence among rural population was 27% and urban 73% while in a study conducted on rural and urban women in Surat showed 52% among rural and 69% among urban. 5 In our study, 56% of the study population had vaginal discharge as the main presenting symptom while in a study performed in peripheral health set ups in Delhi, only 11.2% of women presented vaginal discharge as the main presenting symptom, 3.7% presented lower abdominal pain as the main symptom.…”
Section: Discussioncontrasting
confidence: 43%
“…In our study, multiple sexual partner as a risk factor was found in 15% of the study population, while according to the study in urban Rwanda, it is found to be as high as 33% 4 In our study, STI prevalence among rural population was 27% and urban 73% while in a study conducted on rural and urban women in Surat showed 52% among rural and 69% among urban. 5 In our study, 56% of the study population had vaginal discharge as the main presenting symptom while in a study performed in peripheral health set ups in Delhi, only 11.2% of women presented vaginal discharge as the main presenting symptom, 3.7% presented lower abdominal pain as the main symptom.…”
Section: Discussioncontrasting
confidence: 43%
“…[10] According to their second National Family Health Survey (NFHS-II), nearly 4 out of 10 currently married women in India report at least one reproductive health problem that could [14] A study in Haryana shows that, there is a need for educating school girls about adolescent health and reproductive health problems through schools and parents by the health professional. [15] Absences of reproductive tract infection are essential for the reproductive health of both men and women. It is also critical for their ability to meet reproductive goals.…”
Section: Introductionmentioning
confidence: 99%
“…Kosambiya JK, Vikas K Desai et al tried to estimate the prevalence of reproductive tract infection, sexually transmitted infection among women in urban and rural areas of Surat. 23 They found that bacterial vaginosis was found in 24% of urban and 25% of rural women. They showed a similar prevalence in both groups.…”
mentioning
confidence: 99%